Mapping the Distribution and Population Status of Alosa immaculata and Alosa tanaica (Teleostei, Clupeidae) in the Bulgarian Black Sea Area - Desislava Rozdina; Yana Stoyanova; Georgi Terziyski; Slavi Studenkov; Boris Karakushev; Venceslav Delov; Konstantin Mihaylov; Dimitar Kozhuharov; Yordan Kutsarov; Nikolay Kolev; Nikolay Nedyalkov; Nikolay Natchev (Diversity)
(1) Background: To date, data concerning the population of Alosa immaculata and Alosa tanaica from the marine waters of Bulgaria are rather scarce. In the range of a project for mapping the Bulgarian marine protected sites from the network NATURA 2000, we provide an intense investigation of the biology and distribution of both Alosa species. (2) Methods: A trawling survey was carried out within 102 predefined sampling plots of 10 × 10 km grid cells (93 cells on the continental shelf, up to 100 m depth, and 9 offshore cells). In some coastal regions, sampling was conducted with gill nets of different mesh sizes (28 mm to 36 mm). Analysis of the suitability of the occupied habitat of both species was carried out using the MAXENT v 3.4.0 software application. The status of the populations was studied based on the parameters abundance (ind./km−2), biomass (kg/km−2), size, sex structure, maturity, and food spectrum. (3) Results: Out of 102 transects studied, A. immaculata was found in 12 transects and A. tanaica in 13. A total of 408 fish specimens were captured, out of which 313 were A. immaculata and 95 were A. tanaica. Both species were distributed along Bulgaria’s entire Black Sea coast, with a numerical prevalence of the catches in the southern part. The population size of A. immaculata for the number of individuals on a biographical level in the Marine Black Sea Biographic Region (MBLS) was a minimum of 100,255 individuals and a maximum of 526,408 individuals (the average was 313,286). The population size for A. tanaica was a minimum of 28,183 individuals and a maximum of 449,549 individuals (an average of 238,866). The current population density of A. immaculata in the MBLS was 25.98 ind./km−2, and for A. tanaica, it was 19.00 ind./km−2. The current biomass of the population of A. immaculata in the MBLS was 3.44 kg/km−2, and the population of A. tanaica was 0.53 kg/km−2. The sex ratio for A. immaculata was 1 male:2.6 females, and for A. tanaica, 1 male:3.8 females. Both shad species were feeding with less intensity or not feeding during the winter. The diversity in the food spectrum of A. tanaica was more limited compared to that of A. immaculata. (4) Conclusions: Key parameters for the Bulgarian Black Sea Exclusive Economic Zone indicate current stability in the resources of A. immaculata and A. tanaica and more favorable conditions for the populations in the Natura 2000 sites compared to that outside the Natura 2000. The results of this study should be used to develop management plans for marine protected areas, and future monitoring projects should follow the sampling protocol.